Transperineal drainage of prostate abscesses: A minimally invasive, low‐risk management strategy that yields satisfactory results - David Scholtz; Ali Hooshyari; Lodewikus Petrus Vermeulen; Flavio Vasconcelos Ordones (BJUI Compass, 2024)
Abstract Objectives In this narrative review, we aim to present two cases of transperineal drainage of prostate abscesses with a good clinical outcome. Furthermore, we reviewed the literature on this treatment approach and aim to propose a minimally invasive protocol for managing this rare condition. Patients and Methods Our patients are 33‐ and 61‐year‐old males who both underwent uncomplicated transperineal drainage of prostate abscess with the use of a Precision Point device with rapid clinical improvement and complete resolution of the abscess within the follow‐up period. We used PubMed to conduct a literature search and included and evaluated 16 relevant case reports and case series in which the authors utilized transperineal drainage techniques for prostatic abscesses. Results Our first patient was young and very unwell with sepsis and a pulmonary embolism. He had a complex abscess extending through the prostate to the left pelvic side wall. Trans‐gluteal drainage of the pelvic side‐wall collection was required in addition to transperineal drainage of the prostate abscess. After drainage and a prolonged course of antibiotics, he achieved resolution of the abscess by 7 weeks with ejaculatory function intact. Our second patient who was very keen on the preservation of ejaculatory function had multiple small abscesses and underwent transperineal drainage. He had significant interval improvement of his abscess burden at the 4‐week follow‐up and complete resolution at the 6‐month follow‐up. The total number of cases in the literature on our review is 22, with considerable variability in how the authors managed the prostate abscesses that underwent transperineal drainage, including variability in their follow‐up time frame, choice of imaging modality, duration of antibiotic treatment, drain placement, and use of irrigation solutions (including antibiotics) into the abscess cavity. Furthermore, the sizes of the prostate abscesses were not consistently reported. Given the small sample size and variability in management from different authors, it was not possible to draw any statistical analysis. Conclusion Transperineal prostate abscess drainage combined with prolonged antibiotic therapy provides a less invasive alternative to treating prostate abscesses for those who which to preserve ejaculatory function and avoid the other adverse events of transurethral de‐roofing. In itself, it can achieve complete resolution of abscess. It provides the benefit of drainage under real‐time imaging; for percutaneous drain placement; prevents urethral injury; retrograde ejaculation; and can be done under local anaesthetic which is preferable for the unstable patient. The utility of the procedure may be limited by the complexity of the abscess or whether it has extended beyond the prostate. The patient should always be informed that further drainage via percutaneous methods or transurethral methods may be necessary if their clinical condition does not improve. We recommend this procedure be offered as an alternative to transurethral methods in younger patients and those who would like to preserve ejaculatory function. Furthermore, we highly encourage a prolonged course of antibiotic therapy and interval follow‐up with clinical review of symptoms and imaging to confirm resolution.